The moderating effect of the psychosocial working conditions (effort/reward/overcommitment) on the association between noise annoyance and cognitive performance among adolescents - Noad-Maria Azzi; Sahar Obeid; Rabih Hallit; Diana Malaeb; Sami El Khatib; Mariam Dabbous; Fouad Sakr; Souheil Hallit; Vanessa Azzi (BMC Psychology)
Abstract Objectives The primary objective of the current study was to evaluate the correlation between noise-induced annoyance and the cognitive performance within the Lebanese adolescent population and the moderating effect of psychosocial work aspects-namely effort, reward, and overcommitment- in this association. Methods An anonymous online survey was conducted in Lebanon between April and May 2023, using a snowball sampling technique and distributed across various social media platforms, to gather data from Lebanese adolescents. The sample was composed of 1269 adolescents. Participants voluntarily completed a self-administered Arabic questionnaire that consisted of a sociodemographic section and implemented three scales: Noise Annoyance scale, Effort-Reward in school scale, as well as LEAF scale. Results The moderation analysis findings revealed that at low levels of effort, higher noise annoyance was significantly associated with worse memory function (Beta = 0.94; p =.002) and mathematics skills (Beta = 0.40; p =.002), whereas at low (Beta = 0.49; p <.001) and moderate (Beta = 0.29; p =.001) levels of effort, it was significantly associated with worse sustained sequential processing. At low and moderate levels of reward, higher noise annoyance was significantly associated with worse attention (Beta = 0.48; p <.001 and Beta = 0.20; p <.031 respectively), sustained sequential processing (Beta = 0.43; p <.001 and Beta = 0.22; p =.013 respectively) and working memory (Beta = 0.47; p <.001 and Beta = 0.28; p =.002 respectively). At low levels of reward, higher annoyance was significantly associated with worse memory function (Beta = 0.82; p =.007), processing speed (Beta = 0.38; p =.001) and mathematic skills (Beta = 0.28; p =.026). Finally, at low and moderate levels of overcommitment, higher noise annoyance was significantly associated with worse factual memory (Beta = 0.49; p <.001 and Beta = 0.25; p =.005 respectively), worse attention (Beta = 0.45; p <.001 and Beta = 0.26; p =.005 respectively) and worse processing speed (Beta = 0.43; p <.001 and Beta = 0.23; p =.012 respectively). Conclusion This study could encourage the integration of targeted interventions and strategic measures that address both noise annoyance and psychosocial working conditions, defined as the academic work students perform both at school and at home, to proactively prevent the emergence of cognitive impairment among the adolescent population.